ANALISIS STRUKTUR BANGUNAN TERHADAP ELEMEN HORIZONTAL PADA GEDUNG PENYIMPANAN KPK JAKARTA - Sahat Martua Sihombing; Gita Puspa Artiani; Lydia Darmiyanti (Jurnal Sipil Krisna, 2022)
A storage building is a structure that has specified requirements for usage as a container or location anda high load value. As a result, it is crucial to check or examine the building's structure. There are two separateparts to the building structure, one of which is horizontal. Elements that bear loads working transversely andtransfer the load to a supporting column are known as horizontal elements, sometimes known as bending elements.It is crucial to assess the safety of horizontal elements like beams and slabs since they serve as the floor's bondingand reinforcing frames in superstructures. This final project attempts to assess the shear forces and momentsapplied to the floor slabs and beams, the reinforcement ratio applied to the beams, and the beam deflections thatresult. The presentation in this study makes use of ETABS v.17.0.1 software and secondary data. The 3rd floorhas the largest shear force in the X direction with a value of 59.3292 kN and the largest moment in the X directionwith a value of 128.9298 kN-m, while the 3rd floor has the largest shear force in the Y direction with a value of47.1916 kN and the largest moment in the Y direction with a value of 92.7026 kN-m. According to the result ofETABS v.17.0.1, the beam reinforcement ratio is 0.82 percent, and the maximum deflection permit limit formulauses SNI 2847:2019 to get the permitted deflection value of 25 mm.